Analysis Concepts Redox Using Multiple Representation Based Test Instrument with Computer Based Test (CBT) Model (Universitas Negeri Semarang, 2018)
The research was designed as the method of R&D with the 4D model, define, design, develop and disseminate. The purpose of this research is to develop a diagnostic test instrument two-tier with CBT to diagnose students' understanding profile. The test instrument can be used for the analysis and understanding of the concept Redox with the interpretation of the combination of the students' answers with the class understand the concepts, misconceptions, guessing, do not understand, and do not understand. The results of the feasibility test instrument indicate that the content validity of the category feasible with reliability 0.79. Profile of understanding the concept of students showed which scientific knowledge of which 9 out of 35 students (26.86%), positive misconception that 2 out of 35 students (4.14%), negative misconceptions is one of 35 students (2.43%), the misconception is one of 35 students (1.86%), lucky guess that is one of 35 students (3.71%), lack of knowledge that 12 of 35 students (34.86%), and did not know that 9 out of 35 students (26.14%) the concept of Redox.